2012
DOI: 10.1007/s00464-012-2162-2
|View full text |Cite
|
Sign up to set email alerts
|

The burden of endoscopic retrograde cholangiopancreatography (ERCP) performed with the patient under conscious sedation

Abstract: One-third to one-half of patients experience pain and discomfort during and immediately after ERCP when it is performed with conscious sedation for the patient. Other sedation strategies, such as the use of general anesthesia or propofol, may well reduce the burden of ERCP, particularly for patients with a higher EQ-5D score, younger age, or therapeutic ERCP treatment. However, randomized trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…As a result, 8% required a reversal with flumazenil and/or naloxone 35. Conversely, the inability to safely provide sufficient sedation using conscious sedation results in 40% of patients reporting pain or discomfort during ERCP 4. Intolerance of sedation contributes to more than 30% of failed ERCPs performed under conscious sedation 4 36.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 8% required a reversal with flumazenil and/or naloxone 35. Conversely, the inability to safely provide sufficient sedation using conscious sedation results in 40% of patients reporting pain or discomfort during ERCP 4. Intolerance of sedation contributes to more than 30% of failed ERCPs performed under conscious sedation 4 36.…”
Section: Discussionmentioning
confidence: 99%
“…Conscious sedation has been reported to be inadequate for up to 14% of patients undergoing ERCP 2. Furthermore, up to half of patients undergoing ERCP under conscious sedation experience pain and discomfort during the procedure and postprocedural period 6. Data from Cochrane review showed a better recovery profile among patients receiving propofol, with a comparable safety profile with that of conscious sedation using midazolam and opioid 7.…”
Section: Discussionmentioning
confidence: 99%
“…In patients receiving moderate sedation during ERCP, pain and discomfort during and immediately after ERCP were experienced by one third to one half of the patients due to inadequate level of sedation, as well as inadequate selection of sedative agent against type of procedure and patient physical and mental status. Incremental doses of midazolam lead to unintended deep level of sedation as well as hypotension and desaturation [4]. There was higher failure rate due to premature termination of ERCP because of inadequate sedation [5].…”
Section: Introductionmentioning
confidence: 99%